God the Benefactor and His Human Clients in Rom. 5–8 - Kowalski, Marcin (The Biblical Annals, 2018)
The author applies the patron-client model to read the relationship between God and man in Rom. 5–8. First, the model and its basic features are presented in the context of the Greco-Roman society, including its applicability to divinity. Next, the various elements of the model are traced in Rom. 5–8 (asymmetry, exchange of goods, personal relationship, favoritism, reciprocity, kinship language, honor and voluntary entrance). The article finishes with the advantages of reading Rom. 5–8 through the lens of the patron-client relationship.